Rehabilitation nursing needs in stroke patients with limb dysfunction: A scoping review (脑卒中肢体功能障碍患者康复护理需求的范围综述) - YANG Dan (杨丹); MENG Meiqi (孟美琪); SHEN Wanting (沈婉婷); LI Xuejing (李学靖); HAO Yufang (郝玉芳); FANG Jiaxin (方嘉欣); WANG Fang (王芳) (Association of Integrative Nursing, 2024)
Objective Studies on rehabilitation and nursing of stroke limb dysfunction at home and abroad was searched comprehensively, and the rehabilitation and nursing needs of stroke patients with limb dysfunction were summarized and analyzed, in order to provide reference for future related research. Methods The scoping review method was used to systematically search the Chinese and English databases of CNKI, Wanfang Data, VIP, CBM, PubMed, etc. , from the establishment of the database to July 26, 2021. The subject analysis of the included literatures was conducted based on the framework of the International Classification of Functioning, Disability and Health. Results Totally 19 literatures were included, and the results showed that the rehabilitation nursing needs of stroke patients with limb dysfunction were more diverse and complex, including five needs including disease and rehabilitation knowledge and information needs, activity participation needs, limb function recovery, social environment needs and psychological support needs. Conclusion The rehabilitation nursing needs of stroke patients with limb function are met at a low rate. Medical workers should pay attention to providing patients with diversified knowledge and education, and combine with multidisciplinary teams to develop individualized and scientific and comprehensive rehabilitation and nursing plans for stroke patients with limb dysfunction. (目的 全面检索国内外脑卒中肢体功能障碍康复护理相关研究, 对脑卒中肢体功能障碍患者康复护理需求现状、内容进行总结分析, 以期为今后相关研究提供参考。方法 采用范围综述法, 系统检索中国知网(CNKI)、万方(Wanfang Data)、维普数据库(VIP)、中国生物医学文献数据库(CBM)、PubMed等中英文数据库, 检索时间为建库至2021年7月26日, 并基于《国际功能、残疾和健康分类》(ICF)框架对纳入文献进行主题分析。结果 最终纳入19篇文献, 结果显示脑卒中肢体功能障碍患者康复护理需求种类较多, 且较为复杂, 主要包括疾病及康复知识信息需求、活动参与需求、肢体功能恢复、社会环境需求以及心理支持需求5个需求主题。结论 脑卒中肢体功能患者康复护理需求满足率较低, 医护人员需注重为患者提供多元化的知识教育, 并结合多学科团队, 为脑卒中肢体功能障碍患者制定个体化且科学全面的康复护理计划。)